1998
DOI: 10.1016/s0928-8244(98)00086-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of adhesion of enterotoxigenic Escherichia coli K88 to piglet intestinal mucus by egg-yolk antibodies

Abstract: The objective of the study was to determine if the adhesion of E. coli K88 to piglet intestinal mucus could be inhibited in vitro by spray-dried egg-yolk anti-K88 antibodies. Binding of E. coli was monitored using a radioactive assay. Four 14+/-2-day-old healthy piglets were used for the preparation of mucus from the small intestine. Competition and displacement phenomena were investigated by incubating (a) egg-yolk antibodies and E. coli together prior to adding to the mucus and (b) E. coli and mucus, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 23 publications
(44 reference statements)
1
65
0
Order By: Relevance
“…The isolate, which was obtained from the feces of a piglet suffering from diarrhea, was shown to give a positive agglutination test with anti-K88 ETEC antibody but not with anti-K99 ETEC antibody. E. coli K88ϩMB was tested as the K88ac phenotype (16). Primary cultures of ETEC strains were grown overnight in tryptic soy broth (Difco) at 37°C using a 1% innoculum from stocks stored at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolate, which was obtained from the feces of a piglet suffering from diarrhea, was shown to give a positive agglutination test with anti-K88 ETEC antibody but not with anti-K99 ETEC antibody. E. coli K88ϩMB was tested as the K88ac phenotype (16). Primary cultures of ETEC strains were grown overnight in tryptic soy broth (Difco) at 37°C using a 1% innoculum from stocks stored at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
“…The piglets used in this study were of the K88-susceptible phenotype, since K88-bearing E. coli MB was able to bind to the intestinal epithelial cells when tested microscopically using the procedure described by Wilson and Hohmann (27). The small intestine mucus used in the present study was isolated from piglets by the procedure of Jin et al (16). Briefly, a microscope slide was used to gently scrape the mucosal surface into HEPESHanks' buffer (HH buffer; pH 7.4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IgYs can be generated against colonization factors (outer membrane proteins, fimbriae/pili and lipopolysaccharides), flagella, mucosal receptors, enzymes and toxins important for bacterial survival [40,41].…”
Section: Specific Igy Antibodies Against Pathogens-structure and Funcmentioning
confidence: 99%
“…Feeding the yolk to pigs provides passive immunity to the target disease. Based on this concept, many researches were focused on IgY to prevent E. coli pathogens because diarrhea in neonatal and postweaning pigs is a significant and persistent problem in pig production and among the major causes of diarrhea in piglets are enterotoxigenic E. coli (ETEC) strains expressing K88, K99 and 987P fimbrial antigens (Jin et al, 1998). Several studies showed immuned egg yolk reduces adherence and colonization of ETEC strains, mortality, clinical signs, or diarrhea score in neonatal pigs (Imberechts et al, 1997;Marquardt et al, 1999;Owusu-Asiedu et al, 2002;Zuniga et al, 1997).…”
Section: Dried Eggmentioning
confidence: 99%